Agro‐Waste Extract Based Solvents: Emergence of Novel Green Solvent for the Design of Sustainable Processes in Catalysis and Organic Chemistry. Issue 18 (28th June 2017) - Sarmah, Manashi; Mondal, Manoj; Bora, Utpal
Abstract: Water extract of agro‐waste ash (AWEs) has emerged as an efficient non‐conventional solvent for practicing green reactions in catalysis and organic chemistry. The recent advancements made in the field of agro‐waste‐derived reaction media have witnessed a major advancement in reactions like Suzuki‐Miyaura, Sonogashira, Dakin, Henry, peptide synthesis and ipso ‐hydroxylation. Traditionally, these reactions were conducted in conventional volatile organic solvents (VOCs) derived from non‐renewable petroleum sources. During the course of these reactions AWEs displays distinct properties, such as, in situ base, homogeneous catalyst, nano reactor and reducing agent. This review summarizes the recent developments made in the application of AWEs in important reactions emphasizing on the key utilities and limitations in order to facilitate the further progress of this exciting area of research. Abstract : This review focuses on the recent developments made in the application of Agro‐Waste Extracts (AWEs) as environmentally benign media in organic transformation and emphasizing on their distinctive properties to facilitate the exciting areas of green chemistry research.